Centrally circulating α-klotho inversely correlates with human obesity and modulates arcuate cell populations in mice - Taylor Landry; Peixin Li; Daniel Shookster; Zhiying Jiang; Hongli Li; Brenton Thomas Laing; Wyatt Bunner; Theodore Langton; Qingchun Tong; Hu Huang (Elsevier, 2021)
Objective: Our laboratory recently identified the centrally circulating α-klotho protein as a novel hypothalamic regulator of food intake and glucose metabolism in mice. The current study aimed to investigate novel molecular effectors of central α-klotho in the arcuate nucleus of the hypothalamus (ARC), while further deciphering its role regulating energy balance in both humans and mice. Methods: Cerebrospinal fluid (CSF) was collected from 22 adults undergoing lower limb orthopedic surgeries, and correlations between body weight and α-klotho were determined using an α-klotho enzyme-linked immunosorbent assay (ELISA) kit. To investigate the effects of α-klotho on energy expenditure (EE), 2-day intracerebroventricular (ICV) treatment was performed in diet-induced obesity (DIO) mice housed in TSE Phenomaster indirect calorimetry metabolic cages. Immunohistochemical staining for cFOS and patch clamp electrophysiology were used to determine the effects of central α-klotho on proopiomelanocortin (POMC) and tyrosine hydroxylase (TH) neurons. Additional stainings were performed to determine novel roles for central α-klotho to regulate non-neuronal cell populations in the ARC. Lastly, ICV pretreatment with fibroblast growth factor receptor (FGFR) or PI3kinase inhibitors was performed to determine the intracellular signaling involved in α-klotho-mediated regulation of ARC nuclei. Results: Obese/overweight human subjects had significantly lower CSF α-klotho concentrations compared to lean counterparts (1,044 ± 251 vs. 1616 ± 218 pmol/L, respectively). Additionally, 2 days of ICV α-klotho treatment increased EE in DIO mice. α-Klotho had no effects on TH neuron activity but elicited varied responses in POMC neurons, with 44% experiencing excitatory and 56% experiencing inhibitory effects. Inhibitor experiments identified an α-klotho→FGFR→PI3kinase signaling mechanism in the regulation of ARC POMC and NPY/AgRP neurons. Acute ICV α-klotho treatment also increased phosphorylated ERK in ARC astrocytes via FGFR signaling. Conclusion: Our human CSF data provide the first evidence that impaired central α-klotho function may be involved in the pathophysiology of obesity. Furthermore, results in mouse models identify ARC POMC neurons and astrocytes as novel molecular effectors of central α-klotho. Overall, the current study highlights prominent roles of α-klotho→FGFR→PI3kinase signaling in the homeostatic regulation of ARC neurons and whole-body energy balance.